Tendon-specific activation of tenogenic transcription factors enables keeping tenocytes’ identity in vitro - Chen, Rui; Skutella, Thomas (International journal of molecular sciences, 2022)
We generated a novel tetracycline-inducible transgenic mouse line with the tendon-specific expression of a series of tendon-critical transcription factors. Primary tenocytes derived from this mouse line consistently expressed green fluorescent protein reporter transcription factors in response to doxycycline. The tenocytes maintained their tendon cell properties for a longer time after the transient induction in the absence of growth factors and mechanical stress. Four key transcription factors for tendon development and the green fluorescent protein reporter were linked with different viral 2A self-cleaving peptides. They were expressed under the control of the tet-responsive element. In combination with the expression of BFP, which reports on the tendon-specific collagen I, and mScarlet, which reports on the tendon-specific transcription factor Scleraxis (Scx), we observed the more extended maintenance of the tendon cell identity of in vitro cultured tendon cells and Achilles tendon explants. This means that the Scleraxis bHLH transcription factor (Scx), mohawk homeobox (Mkx), early growth response 1 (Egr1) and early growth response 2 (Egr2) contributed to the maintenance of tenocytes’ identity in vitro, providing a new model for studying extracellular matrix alterations and identifying alternative biomaterials in vitro.